2013
DOI: 10.1177/1077546313483159
|View full text |Cite
|
Sign up to set email alerts
|

Optimal parameters estimation and vibration control of a viscoelastic adaptive sandwich beam incorporating an electrorheological fluid layer

Abstract: The complex shear modulus of an electrorheological (ER) adaptive sandwich beam is optimally estimated to model the system for vibration control. In the composition of a three layered beam, the ER fluid layer is embedded between two constraining layers. Using finite element (FE) method, the governing equations of the composite viscoelastic beam are derived. The developed model is compared with the results found in the literature. In addition, for a fabricated ER sandwich beam, the ASTM E756 standard is employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…They related this anomalous behavior to deviation of beam deformation from the assumptions considered in the American Society for Testing and Materials (ASTM) equations. Allahverdizadeh et al (2013aAllahverdizadeh et al ( , 2013c also employed this technique to characterize ER fluid in the pre-yield region. They reported that the standardized ASTM E756-05:2002 method provides a rough estimation of the storage and loss moduli of the fluid and is not accurate, which is in part attributed to neglecting contribution due to the sealant.…”
Section: Methods Of Characterizing Mr/er Fluids In the Pre-yield Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…They related this anomalous behavior to deviation of beam deformation from the assumptions considered in the American Society for Testing and Materials (ASTM) equations. Allahverdizadeh et al (2013aAllahverdizadeh et al ( , 2013c also employed this technique to characterize ER fluid in the pre-yield region. They reported that the standardized ASTM E756-05:2002 method provides a rough estimation of the storage and loss moduli of the fluid and is not accurate, which is in part attributed to neglecting contribution due to the sealant.…”
Section: Methods Of Characterizing Mr/er Fluids In the Pre-yield Regionmentioning
confidence: 99%
“…Furthermore, this method cannot capture frequency-dependent behavior of the fluid and is more applicable for sandwich structures with solid viscoelastic materials as the core layer. Allahverdizadeh et al (2013aAllahverdizadeh et al ( , 2013bAllahverdizadeh et al ( , 2013c suggested that the ASTM method should be accompanied by an optimization process to update and modify the extracted data. Consequently, they employed particle swarm optimization (PSO) technique to seek optimal storage modulus of the ER fluid by matching the resonant frequencies obtained by theory and experiment.…”
Section: Methods Of Characterizing Mr/er Fluids In the Pre-yield Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the versatile and robust sliding mode control (SMC) methodology [46] will be applied for semiactive aeroelastic response control of the adaptive panel structure. The proposed canonical model is of substantial practical value for structural/aerospace engineers involved in development of dependable analytical and/or experimental tools for design and analysis of tunable ERF-based cylindrical panels with optimal vibrational/aeroelastic characteristics [4,31]. Also, the presented semianalytic time-domain solution can serve as the benchmark for evaluation of stringently numerical or approximate solutions [1,6, 18,32,37,41,50].…”
Section: Introductionmentioning
confidence: 99%
“…Such unique characteristics along with the inherent ability of electro-rheological fluids to interface with modern control systems make them very useful in numerous vibration and noise control applications (e.g., shock absorbers, vibration damping devices, brakes, clutches, actuators, sensors, servovalves, robotic joints, muscle stimulators [26,30,34,47]). Many researchers have studied active or semi-active vibration suppression of electro-rheological-based structures using various control strategies [4,14,16,47,48]. For example, in a series of recent research works, Hasheminejad and coworkers [19,21,22] applied the Hamilton's principle, the Runge-Kutta time integration algorithm, and the sliding mode control (SMC) strategy, for semi-active supersonic flutter response control of ERF-based sandwich flat panels and circular cylindrical shells.…”
Section: Introductionmentioning
confidence: 99%